Efficacy of combination therapy of vitamin D and bisphosphonates in the treatment of postmenopausal osteoporosis: a systematic review and meta-analysis - Yang, Yuangui; Yang, Mingyue; Su, Xuanyi; Xie, Feibin (Frontiers in Pharmacology, 2024)
Objective: There is currently no consensus on whether the combination therapy of Vitamin D (VitD) and bisphosphonates offers superior efficacy compared to monotherapy in the treatment of postmenopausal osteoporosis. The aim of this study is to conduct a meta-analysis of recent relevant research to synthesize the available evidence and further investigate whether the combined use of VitD and bisphosphonates is superior to monotherapy in treating osteoporosis in postmenopausal women. Methods and Results: We systematically searched PubMed, EMBASE, the Cochrane Library, and Web of Science for randomized controlled trials (RCTs) comparing the effects of monotherapy with VitD or bisphosphonates versus their combination therapy in the treatment of postmenopausal osteoporosis, up to February 1, 2024. The articles were independently screened and relevant data were extracted by two investigators. The changes in mean values and percentage changes for bone resorption markers, bone formation markers, bone mineral density, and bone mineral metabolism markers were expressed using the standardized mean difference (SMD) and 95% confidence intervals (CI). Heterogeneity was quantitatively described using the I2 test. Subsequently, sensitivity analyses were performed for data with significant heterogeneity. Subgroup analyses were conducted based on the type of monotherapy used, and potential publication bias was assessed. The analysis revealed that the combination of VitD and bisphosphonates demonstrated a more pronounced effect in increasing alkaline phosphatase (ALP), 25-hydroxyvitamin D (25-OH-VD), and serum calcium (sCa) levels, as well as in decreasing levels of serum bone-specific alkaline phosphatase (sBALP), serum C-terminal telopeptide of type I collagen (sCTX), and urinary N-telopeptide of type I collagen (UriNTX) compared to the monotherapy group. However, the combination of VitD and bisphosphonates did not show a significant advantage over monotherapy in terms of improving osteocalcin levels. The differences in the mean changes in osteocalcin, UriNTX, and sCa, as well as the percentage changes in parathyroid hormone (PTH) were not statistically significant (p > 0.05). Conclusion: The meta-analysis suggests that compared to monotherapy, the combination therapy of VitD and bisphosphonates exhibits a more favorable effect on bone mineral density and bone calcium metabolism-related markers in the treatment of postmenopausal osteoporosis.